Advanced Design and Fabrication of Islamic Tile Ceramic Wall Tiles With Indonesian Batik Patterns Using Artistic CAD/CAM and 3D Printing Technology - Anggoro, P. W.; Yuniarto, T.; Bawono, B.; Setyohadi, D. B.; Felasari, S.; Widyanarka, O. D. W.; Tauviqirrahman, M.; Jamari, J.; Bayuseno, A. P. (Frontiers in Mechanical Engineering, 2022)
The ceramic tile wall is a decorative element used inside restaurants, museums, hotels, aristocratic residences, and places of worship. It plays a critical role in the development of a structure with strong personality and unique qualities by providing relief patterns specific to history or era. The demand for distinctive ornamental wall ceramics that can be mass produced with precision and accuracy has been a challenge for numerous ceramic enterprises in Indonesia, which have historically relied on the skills of artistic professionals in a handmaking process. The purpose of this research was therefore to develop and apply a ceramic tile design process that integrates computer design and fabrication methods with traditional ceramic production techniques. Using the ArtCAM 2015R2 software, photos of batik and Islamic themes were effectively converted into a 2.5D computer-aided design model. Additive manufacturing technology was then used in conjunction with Objet30 Pro 3D printer to precisely produce master molds with Islamic nuances such as puzzle and floral patterns, then conventional ceramic fabrication technology was employed to produce ceramic tiles using these molds. By combining computer-aided design and rapid prototyping technologies, a variety of exact and detailed Islamic decorative ceramic wall tiles were produced with dimensional accuracies within 2.00 mm. Furthermore, the proposed approach demonstrated a 90% reduction in design-to-production time from to 10–12 months to roughly 1–1.5 months